Gambaran kebiasaan buruk dan kejadian maloklusi pada siswa Sekolah Dasar Negeri 19 Pemecutan - Helda Cecilia Susanto; Putu Ika Anggaraeni; Ni Kd Fiora Pertiwi (School of Dentistry Faculty of Medicine Udayana University, 2019)
Introduction: Dental malocclusion is a deviation of teeth disposition and malrelation of dental arches and jaw beyond acceptable limit of conformity. Malocclusion is formed as a result of multifactorial interactions, either external or internal. Suspected external factors as the cause of malocclusion are oral habits, such as thumb or finger sucking, putting foreign objects into the oral cavity (biting pencils, pens and nails), tongue sticking or tongue thrusting, mouth breathing, and lip sucking or lip biting. The purpose of this study is to evaluate correlation of bad habits towards malocclusion in students of SDN 19 Pemecutan. Method: Descriptive analytic study with cross sectional design was used as the study method. Sampling technique used was total sampling with total of 87 samples of children. Data of bad habit and the incidence of malocclusion were obtained by using questionnaires and HMAR (Handicapping Malocclusion Assessment Record) index. Data was analyzed using chi square test. Result: The results of this research exhibited that respondents conducted bad habits were 23 students (26.4%). Respondent who conducted bad habits and had malocclusion was as many as 13 students (16.7%). Based on statistical test using chi square, p-value = 0.002 (p <0.05) was obtained, which mean there was relationship of bad habits towards incidence of malocclusion in SDN 19 Pemecutan. Conclusion: It is concluded that there is relationship between bad habits towards incidence of malocclusion in students of SDN 19 Pemecutan.